Carbon dioxide generation rates of different age and gender under various activity levels. (December 2020) - Yang, Liu; Wang, Xueni; Li, Minghui; Zhou, Xiang; Liu, Shichao; Zhang, Hui; Arens, Edward; Zhai, Yongchao
Abstract: Indoor carbon dioxide (CO2 ) is a critical parameter in the design and control of ventilation, and in monitoring fresh air levels in buildings. Building occupants are primary sources for indoors CO2, and the rate at which CO2 is generated depends on the occupants' physical activities. In the past, CO2 generation rates have been indirectly calculated from metabolic rate data. There has been little systematic experimental determination of human CO2 generation rates at different activity levels. This study experimentally determines human CO2 generation rates for use in building design and control applications. CO2 generation rates were obtained by a high accuracy indirect calorimetry system on 99 human subjects aged from 20 to 70, who were asked to perform 18 activities (including office, household, and walking activities) in a climatic chamber controlled at 26 °C. CO2 generation rates increase significantly as activity levels increase. Age was found to have a small effect, while gender differences were significant. Women produced less CO2 than men at the same activity levels, mainly attributable to their lower body masses. Regression models were developed based on activity levels and age for each gender to predict CO2 generation rates. Significant discrepancies were found between measured CO2 generation rates predicted by the models in ASHRAE 62.1–16 and ASTM D6245-18, especially at higher activity levels. These findings provide fundamental data for designers and researchers in ventilation and indoor air quality field, and future ventilation standard revisions. Highlights: Experimental study using human subjects with aged 20–70 years. CO2 generation rates measured directly from light to moderate activity levels. Age has a small effect while gender effect is significant. Males generate more CO2 than females at the same activity levels. Significant discrepancies between measured and standard values.